THE VALUE AND IMPORTANCE OF ANAMNESIS IN THE DIFFERENTIAL DIAGNOSIS OF TEMPOROMANDIBULAR DISORDERS - Makieiev, V.F.; Telishevska, O.D.; Mykhailevych, M.Yu. (World of Medicine and Biology, 2021)
Despite the fact that a significant amount of research has been devoted to the study of temporomandibular disorders, the etiology and pathogenesis still remain not fully determined. The aim of our study was to determine the factors of the anamnestic data of patients that may affect the onset and development of temporomandibular disorders. The subjects of the study were 178 people with suspected temporomandibular disorders, who underwent a set of examinations. According to the anamnestic data of patients, we performed an analysis of possible factors that could provoke the development of temporomandibular disorders. However, after a comparative analysis of the main group and the comparison group, we did not find statistically significant differences (p>0.05) between the indicators of these groups, except for such a feature as “bruxism”, which indicates the uncertainty of these factors in regards to having possible influence on the development of temporomandibular disorders in our research. Thus, it is possible to assume that certain diseases could cause disorders of the temporomandibular joint, yet it is impossible to rule out isolated disorders of the joints. Comprehensive study of the influence of anamnesis on the diagnosis and differential diagnosis of temporomandibular disorders remains open and requires further research.